Depressive Symptoms Are Positively Associated with Time Spent Sedentary in Healthy Young US Adults. Issue 2 (February 2017) - Brazendale, Keith; Drenowatz, Clemens; Falck, Ryan S.; Randel, Allison B.; Hoffmeyer, Jared D.; Hand, Gregory A.; Burgess, Stephanie; Blair, Steven N.
Abstract : Introduction: Sedentary time and depressive symptoms are positively associated in elderly adults and adults with chronic disease; however, little is known about this relationship in generally healthy young adults. The purpose of this study was to investigate the association between objectively measured sedentary time and depressive symptoms in a large sample of healthy young adults. Methods: Time spent sedentary and in moderate-to-vigorous physical activity (MVPA) was measured in 430 participants (49% men; 28 ± 4 years; 25.5 ± 3.3 kg/m 2 ) using the SenseWear Mini Armband over a 10-day period. The Profile of Mood States depression scale was administered to assess depressive symptoms. Independent samples t tests investigated differences in MVPA, time spent sedentary, and Profile of Mood States scores between males and females. Linear regression analyses, adjusting for MVPA, sex, and body mass index, were employed to examine associations between sedentary time and depressive symptoms. Results: Mean time spent sedentary while awake was 681 ± 94 min/d. Holding MVPA constant, depressive symptoms were positively associated with sedentary time (β = 1.80; P < 0.01; R 2 = 0.54). This association was statistically significant in males (β = 2.06; P < 0.01; R 2 = 0.59) but not females ( P = 0.10). Conclusions: Depressive symptoms are positively associated with time spent sedentary in healthy young US adults, independent of MVPA, particularly in men. A reduction in sedentary time may provide a valuable, low cost, option in the prevention of depressive symptoms.